2012
DOI: 10.1002/lary.23562
|View full text |Cite
|
Sign up to set email alerts
|

A new paradigm for the diagnosis and management of unknown primary tumors of the head and neck: A role for transoral robotic surgery

Abstract: Objectives/Hypothesis: In 2% to 3% of patients with cancer metastatic to cervical lymph nodes, a primary tumor will not be found despite exhaustive diagnostic efforts. The treatment for these patients includes cervical lymphadenectomy followed by radiation to areas with increased risk of harboring a mucosal primary. Wide-field radiation therapy increases the incidence of xerostomia and dysphagia. Localizing a primary tumor has thus both therapeutic and quality-of-life implications, allowing possible complete s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
184
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(200 citation statements)
references
References 27 publications
3
184
0
6
Order By: Relevance
“…Mehta et al reported 10 patients underwent transoral robotic base of tongue CT, computed tomography; MR, magnetic resonance; FDG-PET, 18-fluoro-deoxyglucose positron emission tomography. resection (26). All patients underwent a cervical biopsy, PET/CT, formal endoscopy and bilateral tonsillectomy before this procedure but not identified primary lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Mehta et al reported 10 patients underwent transoral robotic base of tongue CT, computed tomography; MR, magnetic resonance; FDG-PET, 18-fluoro-deoxyglucose positron emission tomography. resection (26). All patients underwent a cervical biopsy, PET/CT, formal endoscopy and bilateral tonsillectomy before this procedure but not identified primary lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies suggest that transoral laser microsurgery (TLM) or transoral robotic surgery (TORS) is more effective for the identification of a primary in the oropharynx especially in the base of tongue (BOT) in patients with suspected CUP [37,38]. Recent case series have reported high rates of detection ranging from 86 to 94% including TLM [38,39] and 72 to 90% including TORS [37,38,40] in the diagnostic work-up of patients with suspected CUP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent case series have reported high rates of detection ranging from 86 to 94% including TLM [38,39] and 72 to 90% including TORS [37,38,40] in the diagnostic work-up of patients with suspected CUP. According to Durmus et al [41] the PT was identified in 77% of patients (17 of 22) with 80% HPV-positive LNM residing in the palatine tonsil in 59% (13 of 22), and the BOT in 18% (4 of 22).…”
Section: Discussionmentioning
confidence: 99%
“…TORS is currently being used in the management of early-stage tumors, more advanced malignancies, tumor recurrences, deep neck space infections, tumors of unknown primary site, and comparatively benign conditions such as obstructive sleep apnea [1,[15][16][17][18]. The incidence of postoperative complications seen with TORS is generally low and has the potential to be further reduced by increased experience with the technique and an appreciation of risk factors for the most common issues [5,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%